Psychometric evaluation of the medical outcome study (MOS) social support survey among Malay postpartum women in Kedah, North West of Peninsular Malaysia - Wan Mahmud, Wan Mohd Rushidi; Awang, Amir; Mohamed, Mahmood Nazar (Universiti Sains Malaysia, 2004)
The Malay version of the Medical Outcome Study (MOS) Social Support Survey was validated among a sample of postpartum Malay women attending selected health centers in Kedah, North West of Peninsular Malaysia. 215 women between 4 to 12 weeks postpartum were recruited for the validation study. They were given questionnaires on socio-demography, the Malay-versions of the MOS Social Support Survey, Edinburgh Postnatal Depression Scale (EPDS) and the 21-items Beck Depression Inventory-II (BDI-II). 30 of the women, who were bilingual, were also given the original English version of the instrument. A week later, these women were again given the Malay version of the MOS Social Support Survey. The scale displayed good internal consistency (Cronbach’s alpha = 0.93), parallel form reliability (0.98) and test-retest reliability (0.97) (Spearman’s rho; p<0.01). The negative correlations of the overall support index (total social support measure) with the Malay versions of EPDS and BDI-II confirmed its validity. Extraction method of the 19 items (item 2 to item 20) from the MOS Social Support Survey using principle axis factoring with direct oblimin rotation converged into 3 dimensions of functional social support (informational, affectionate / positive social interaction and instrumental support) with reliability coefficients of 0.91, 0.83 and 0.75 respectively. The overall support index also displayed low but significant correlations with item 1 which represents a single measure of structural social support in the instrument (p <0.01). The Malay version of the MOS Social Support Survey demonstrated good psychometric properties in measuring social support among a sample of Malay postpartum Malay women attending selected health centers in Kedah, North West of Peninsular Malaysia and it could be used as a simple instrument in primary care settings.